2016
DOI: 10.1016/j.sbspro.2016.05.106
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intellectual Capital on Organizational Performance

Abstract: In the field of organizational performance, managers always need to be aware of the importance of accounting in economy for decision-making in economic units, financial reports being considered an index for decision-making of investors. However, in the knowledge era, where intellectual capital represents a large part of the value of a product, the traditional annual financial statements report only partially the value of intangible assets (concessions, licenses, patents, trademarks, etc.). In fact, intellectua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
2
29

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 12 publications
6
94
2
29
Order By: Relevance
“…The R-squared indicated the amount of variance described by the access of variables in Step 1 and Step 2 of the hierarchical regression. Gogan, Artene, Sarca, and Draghici (2016) state R-squared is a proper indicator to explain the size of the effect. According to Cohen (1988), R-squared can be evaluated as 0.0196 small effect, 0.13 medium effect and 0.26 large effect.…”
Section: Resultsmentioning
confidence: 99%
“…The R-squared indicated the amount of variance described by the access of variables in Step 1 and Step 2 of the hierarchical regression. Gogan, Artene, Sarca, and Draghici (2016) state R-squared is a proper indicator to explain the size of the effect. According to Cohen (1988), R-squared can be evaluated as 0.0196 small effect, 0.13 medium effect and 0.26 large effect.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to notice that today's strategic financial decisions are made in a changing dynamic environment, so innovation, particularly in the field of finance are important (gsb.stanford.edu). Intellectual capital, as an intangible asset has an important role for organizations which want to be efficient on the market and to obtain sustainable competitive advantage (Gogan et al, 2016). For the two highest levels of agreement on the Likert scale being aggregated, the most significant impact of financial decision-making is on the factors 'intellectual capital' and 'the speed of decision-making'.…”
Section: Research Resultsmentioning
confidence: 99%
“…Research is also conducted Hashim et al, (2015) who found that intellectual capital has a significant influence on organizational performance in Malaysia. Other research conducted by Gogan et al, (2016) found a significant relationship between intellectual capital and organizational performance.…”
Section: Introductionmentioning
confidence: 76%